2019
DOI: 10.3390/ijerph16245040
|View full text |Cite
|
Sign up to set email alerts
|

Critical Appraisal of Qualitative Studies of Muslim Females’ Perceptions of Physical Activity Barriers and Facilitators

Abstract: Muslim women's perceptions of cultural, religious, and secular determinants of physical activity have been studied for many years, with information typically acquired through focus groups or interviews. Multiple reviews synthesizing the research have been published, however, individual studies have not been scrutinized for their quality/rigor. Therefore, I critically appraised the quality of the body of qualitative research studies that utilized focus groups to identify Muslim women's perceptions of physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Interventions to encourage the engagement of Muslim women in physical exercise should address the multiple layers of the socioecological model to redress the main barriers at different levels. These different levels of barriers include intrapersonal barriers, such as lack of self-efficacy, motivation, and knowledge; interpersonal barriers, such as lack of social support; and environmental barriers, such as lack of affordable facilities appropriate for the cultural and religious beliefs regarding the participation of women with gender-sensitive and modest dress [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interventions to encourage the engagement of Muslim women in physical exercise should address the multiple layers of the socioecological model to redress the main barriers at different levels. These different levels of barriers include intrapersonal barriers, such as lack of self-efficacy, motivation, and knowledge; interpersonal barriers, such as lack of social support; and environmental barriers, such as lack of affordable facilities appropriate for the cultural and religious beliefs regarding the participation of women with gender-sensitive and modest dress [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, there was a lack of transparency on how the data was analysed and its underpinning theory. The two studies [26,45] with the lowest scores were deemed to have poor reporting of their studies and were excluded from the analyses and results [46].…”
Section: -Prisma Diagram)mentioning
confidence: 99%
“…A systematic review of 22 studies published since 2000 identified numerous determinants of PA participation among immigrant women including individual (lack of time, health status, motivation), familial (family support) and environmental (seasonality, neighbourhood, social support) factors [ 9 ]. Other studies involving qualitative interviews revealed that gender (sacrifice self-care for household/family), culture (PA not encouraged) and socioeconomic (low-paying/multiple jobs) factors contribute to low PA rates among immigrant women [ 10 , 11 ]. Immigrant women are also hard-to-reach due to low help-seeking arising from mistrust of healthcare providers and poor healthcare experiences [ 12 ].…”
Section: Introductionmentioning
confidence: 99%